The thread of life : the story of genes and genetic engineering - Aldridge, Susan (Cambridge University Press, 1996)
Susan Aldridge gives an accessible guide to the world of DNA and also explores the applications of genetic engineering in biotechnology. She takes the reader, step by step, through the fascinating study of molecular biology. The first part of the book describes DNA and its function within living organisms. The second part explores genetic engineering and its applications to humans such as gene therapy, genetic screening and DNA fingerprinting. The third looks at the wider world of biotechnology and how genetic engineering can be applied to such problems as producing vegetarian cheese or cleaning up the environment. The final part explains how knowledge of the structure and functioning of genes sheds light on evolution and our place in the world. Although easy to read, this book faces up to the science involved and should be read by anyone who wants to know about DNA and genetic engineering.